Wavelet Analysis Method to Solve the Problem of Wireless Location Tracking - Baoquan Chen; Yongyi Mao (Dianxin kexue)
The signal of non-line-of-sight propagation（NLoS）largely determine the positioning accuracy of the mobile station in wireless location,the wavelet analysis theory has obvious advantages in signal processing.A positioning and tracking algorithm of the mobile station（MS）in the NLoS environment of cellular network was presented.Using wavelet transform signal decomposition and reconstruction,the TDOA measurement error correction,re-use classic Chan algorithm to estimate the location of the mobile station,with the corresponding distance threshold to track the location of the mobile station location.The simulation results show that the algorithm can effectively achieve the static positioning and dynamic tracking of the location of the mobile station,and significantly better than the classical algorithm simulation results in the same environment,and effectively improve the positioning accuracy.